Influencia de la calidad de servicio en la imagen corporativa de la empresa Compartamos Financiera - Trujillo. - Antonio Miranda, Claudia Isabel (2014)
The present research work aims to determine the influence of the quality of service in the corporate image of the company share financial district of Trujillo, since it is currently becoming an essential requirement to compete both in the short and long term, being a strategic element and a distinctive advantage. This research has been developed the design of transverse descriptive investigation, as well as inductive methods; analytical, statistical and research data collection, as the survey technique. After having obtained information from 352 clients, the surveys applied, he emphasized empathy as one of the most important aspects followed by response capacity, security, reliability and tangibility, it is necessary to highlight the issue of perceived service, kindness, interest, respect, is maintained between the company and employees, in order to be able to develop a better quality of service attendance. After having obtained information from 352 clients, the surveys applied, he emphasized empathy as one of the most important aspects followed by response capacity, security, reliability and tangibility, it is necessary to highlight the issue of perceived service, kindness, interest, respect, is maintained between the company and employees, in order to be able to develop a better quality of service attendance.